2004
DOI: 10.1083/jcb.200303037
|View full text |Cite
|
Sign up to set email alerts
|

Role of the hydrophobic domain in targeting caveolin-1 to lipid droplets

Abstract: Although caveolins normally reside in caveolae, they can accumulate on the surface of cytoplasmic lipid droplets (LDs). Here, we first provided support for our model that overaccumulation of caveolins in the endoplasmic reticulum (ER) diverts the proteins to nascent LDs budding from the ER. Next, we found that a mutant H-Ras, present on the cytoplasmic surface of the ER but lacking a hydrophobic peptide domain, did not accumulate on LDs. We used the fact that wild-type caveolin-1 accumulates in LDs after brefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
80
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 52 publications
5
80
0
1
Order By: Relevance
“…Some of the best characterized are the hydrophobic domains of caveolin-1 and caveolin-2, which have been shown to be necessary to target these proteins to lipid droplets (18,19). Although caveolins differ from viperin in that they encode two hydrophobic domains that insert into membranes and generate a cytosolic hairpin, altering hydrophobic residues within these domains prevented caveolin-1 or caveolin-2 from associating with lipid droplets (18,19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the best characterized are the hydrophobic domains of caveolin-1 and caveolin-2, which have been shown to be necessary to target these proteins to lipid droplets (18,19). Although caveolins differ from viperin in that they encode two hydrophobic domains that insert into membranes and generate a cytosolic hairpin, altering hydrophobic residues within these domains prevented caveolin-1 or caveolin-2 from associating with lipid droplets (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Although caveolins differ from viperin in that they encode two hydrophobic domains that insert into membranes and generate a cytosolic hairpin, altering hydrophobic residues within these domains prevented caveolin-1 or caveolin-2 from associating with lipid droplets (18,19). Furthermore, these analyses indicated that the packing of the hydrophobic residues in these domains is specifically important for localizing to lipid droplets, as altering some of these residues did not affect association with other membranes, such as the plasma membrane and Golgi (19). Because lipid droplets are derived from ER membranes, the packing and hydrophobicity of the N-terminal amphipathic ␣-helices of viperin and NS5A may be suited for binding to both the ER and lipid droplets and may facilitate their localization to lipid droplets in the context of infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DGAT2 has a potential proline knot with 5 proline residues from amino acids 329 and 350. Other proteins, including perilipin, caveolin, AAM-B, and viperin are directed to lipid droplets by distinct hydrophobic sequences (33,(63)(64)(65). DGAT2 has a moderately hydrophobic region between amino acids 230 and 250 that may interact with the lipid droplet surface (20).…”
Section: Discussionmentioning
confidence: 99%
“…5B) even though the N terminus of caveolin-1 is supposed to be exposed for digestion. Caveolin-1 adopts a hairpin topology with both ends facing the cytosolic side of the plasma membrane (21,22). If the membranes were ruptured by 0.5% CHAPS, caveolin-1 and the RTN3 fragments would be further digested by proteinase K (Fig.…”
Section: The Orientation Of the C-terminalmentioning
confidence: 99%